The Coincidence of Necrotizing Enterocolitis and Rotavirus Infections and Potential Associations with Cytokines - Efsun Sızmaz; Mehmet Satar; Ferda Özlü; Akgün Yaman; Hacer Yapıcıoğlu Yıldızdaş; Kenan Özcan (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Necrotizing enterocolitis (NEC) is the most common gastrointestinal disease in neonatal intensive care units. Although the pathogenesis of NEC remains unclear, evidence suggests that infections, especially bacterial infections, may play an important role. Viral infections may also result in NEC. Several outbreaks of NEC associated with rotaviruses have been described previously.